Legis Ratio of Legal Protection of Local Food - Syaharie Ja’ang,; Slamet Suhartono,; Endang Prasetyawati,; Yovita Arie Mangesti, (Technium Social Sciences Journal, 2022)
This study aimed to analyze and find the legal protection ratio of local food. This research uses normative legal research methods, namely legal analysis based on positive legal studies or norms of legislation. The conclusions in this study are (1) The existence of local food is regulated in the formulation of article 12 paragraph (3) of Law number 18 of 2012 concerning food. Still, there is no formulation of articles that specifically regulate the protection of food law in the food law. local, or there is still a void in legal norms. (2) The concept of legal protection for local food is based on justice, namely: (a) Producers (business actors) and local food farmers are protected by their rights and feel safe, both physically and mentally. (b) Legal protection for consumers and producers in buying and selling local food and local food products and the freedom to enjoy their rights, as long as they do not conflict with the laws and regulations. (c) Guarantee of legal protections to prevent abuse of local food or local food products, (d) create order in developing local food and prevent arbitrary acts by local government officials, (e) Realize the responsibility of producers (business actors) to food distribution local and local food products based on distribution permits, (f) Creating compliance of producers (business actors), consumers and local food farmers to the provisions of the legislation.